The Effect of Treatment by Diclofenac with Iontophoresis in Osteoarthritic Knee - Luangpukdee, Sudjai (Journal of Health Science of Thailand, 2017)
A quasi-experimental research, pre-post test control group design was to compare treatment outcome between two groups undergoing hot pack in conjunction with ultrasound wave with and without diclofenac with iontophoresis. The samples included 42 osteoarthritis knee patients for each group treated at department of physical therapy in Ban Pong hospital during January - May 2012, a time / day for 5 consecutive times. Collected data used the modified WOMAC scale, were analyzed using mean, paired t-test and independent t-test, chi-square, Mann Whitney U. The results showed that after treatment in the experimental group had average score of pain dimension, stiffness dimension decreased and function dimension increased significantly (p < 0.001). Comparisons between the two groups showed that after treatment in the experimental group had average score of pain dimension, stiffness dimension decreased and function dimension increased than the control group (p < 0.05).